(untitled) (International Journal of Engineering Sciences & Management Research, 2016)
Library in early days was thought to be the “Storehouse of Knowledge”, butgradually changed into “Powerhouse of knowledge”. The information or knowledge is increasingly becoming the basic source of expansion of different discipline, innovation and discoveries. Therefore, modern society is known as information society. Information is treated as an economic commodity. Production, distribution and consumption of information have increased enormously to support the day to day activities of the society. Hence, it is essential for library personal to develop different products and services to run an academic library efficiently and effectively. An attempt has been made to investigate the existing ICT related infrastructural facilities/services available in the Library and Information Centre in the study area.